Les socialismes en Grande-Bretagne, 1850-1914 - Alexandra Sippel (Revue Française de Civilisation Britannique)
In the second half of the nineteenth century, British socialism was diverse. New movements emerged to demand a more democratic representation for workers. Socialist groups agreed on the need to nationalise the land and means of production in order to achieve a fair distribution of wealth for those who produced it. Yet there were marked divergences regarding the role of the workers and the strategies most likely to achieve that fair distribution. Marxist socialism, Fabian socialism, trade unionism and new syndicalism provided different and complementary answers, and attempted to merge into the Labour Representation Committee that gave birth in 1906 to the Labour party.